The Impact of Destination Image on Revisit Intention Mediation Role by Overall Satisfaction Perspective from Shopping Destination in Bandung, Indonesia - Bob Foster; Iwan Sidharta (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
Currently, the tourism sector is a central issue in the growth of a country. Researchers have proven the critical role of the tourism sector in increasing state revenues through tourist visits, both domestic and foreign tourists. Several previous studies have shown the part of the destination image in increasing the revisit rates. However, multiple research models have differed variations in explaining the influence of the destination image on the tourists' loyalty to revisit shopping destinations. Therefore, this study aims to determine the effect of destination image on tourist revisit intention towards shopping tours in Bandung. The survey approach is used to answer the research objectives. The results prove there is an influence of the destination image on the tourists' revisit intention to shopping tours with 179 samples carried out simultaneously on several shopping tourist destinations in Bandung. Thus, the proper advice to improve the revisit intention is providing facilities and infrastructure as well as exciting experiences for the tourists.